2019
DOI: 10.3390/w11051065
|View full text |Cite
|
Sign up to set email alerts
|

Stable Hydrogen and Oxygen Isotope Characteristics of Bottled Water in China: A Consideration of Water Source

Abstract: The origin of bottled water can be identified via its stable isotope signature because of the spatial variation of the stable isotope composition of natural waters. In this paper, the spatial pattern of δ2H and δ18O values were analyzed for a total of 242 bottled water samples produced at 137 sites across China that were randomly purchased during 2014–2015. The isotopic ratios of bottled water vary between −166‰ and −19‰ for δ2H, and between −21.6‰ and −2.1‰ for δ18O. Based on multiple regression analyses usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…Due to differences in water vapor evaporation, transport, mixing, and condensation processes under different spatiotemporal conditions, the 2 H and 18 O in local water often exhibits spatial heterogeneity . Research has found that the δ 18 O and δ 2 H values in some of the mountainous locations in the northeast and northwest of China were significantly lower than in the low elevation areas . Water isotope values decrease from the southeastern coastal regions with heavy precipitation toward the North China Plain northwestern regions .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to differences in water vapor evaporation, transport, mixing, and condensation processes under different spatiotemporal conditions, the 2 H and 18 O in local water often exhibits spatial heterogeneity . Research has found that the δ 18 O and δ 2 H values in some of the mountainous locations in the northeast and northwest of China were significantly lower than in the low elevation areas . Water isotope values decrease from the southeastern coastal regions with heavy precipitation toward the North China Plain northwestern regions .…”
Section: Resultsmentioning
confidence: 99%
“…52 Water isotope values decrease from the southeastern coastal regions with heavy precipitation toward the North China Plain northwestern regions. 52 In the higher latitude areas of North China, as the temperature decreases, δ 2 H and δ 18 O precipitation values gradually decrease due to altitude effects, latitude effects and temperature effects on a geographical scale. 52 Therefore, there will be differences in the δ 2 H and δ 18 O values of rice from different regions.…”
Section: Rice δ 2 H and δ 18 O Fractionation Characteristics And Theirmentioning
confidence: 99%
See 1 more Smart Citation
“… Global bottled water consumption has largely increased (14.35 billion gallons in 2020) [1] , [2] , [3] , [4] , [5] during the last decade since consumers are demanding healthier and safer forms of rehydration. Bottled water sources are normally labeled as mountainous and pristine mineral springs (fed by rainfall and snow/glacier melting processes), deep groundwater wells or industrial purified water.…”
mentioning
confidence: 99%